Effect of Interactive Communication and System Management Training Continuity on performance of tea firms in Nandi County, Kenya - Bett, Peter; Bor, Gilbert; Jemaiyo, Beatrice (Research Journal in Advanced Social Sciences, 2023)
Training on ISO 22000:2018(E) and organizational performance are closely linked. Yet, smallholder tea farmers in Nandi County still face challenges regarding quality. The purpose of this study was to explore the effect of continuous training of ISO 22000:2018(E) certification on performance. This paper examines two variables from the stud, namely interactive communication training continuity and system management training continuity, and how they impact organizational performance. The study used cross-sectional study design and targeted 2988 employees out of which 353 were sampled through proportionate random sampling technique. Primary data and questionnaires were used. Validity was ensured through expert judgement. Reliability test through Cronbach’s test yielded a coefficient of more than 0.7. Data was analysed using stepwise multiple linear regression. The study discovered that continuous training of ISO 22000-2018(E) explained 99.9% (R2=0.999) variation of performance. Specifically, interactive communication training had an insignificant effect on performance (β =-.034, p=0.842). The study concluded that system management training continuity and system management training continuity have some roles to play in organizational performance of tea firms. It was thus recommended that the tea firms should ensure that interactive communication training continuity is enhanced to improve the organizational performance. Further, tea firms should also ensure that system management training continuity is enhanced within the tea firms and across the value chain.